Comparative Analysis of Salivary Mycobiome Diversity in Human Immunodeficiency Virus-Infected Patients - Chang, Shenghua; Guo, Haiying; Li, Jin; Ji, Yaoting; Jiang, Han; Ruan, Lianguo; Du, Minquan (Frontiers in Cellular and Infection Microbiology, 2021)
Reports on alterations in the oral mycobiome of HIV-infected patients are still limited. This study was designed to compare the salivary mycobiome between 30 human immunodeficiency virus (HIV) infections and 30 healthy controls and explore the effect of antiretroviral therapy (ART) administration on the oral mycobiome of HIV infections. Results showed that the diversity and richness of salivary mycobiome in HIV-infected individuals were higher than those of controls (P < 0.05). After ART, the diversity and richness of salivary mycobiome in HIV-infected patients were reduced significantly (P < 0.05). Candida, Mortierella, Malassezia, Simplicillium, and Penicillium were significantly enriched in the HIV group and dramatically decreased after ART. While the relative abundance of Verticillium, Issatchenkia, and Alternaria significantly increased in patients with HIV after ART. Correlation analysis revealed that Mortierella, Malassezia, Simplicillium, and Chaetomium were positively correlated with viral load (VL), whereas Thyrostroma and Archaeorhizomyces were negatively related to VL and positively related to CD4+ T-cell counts. All results showed that HIV infection and ART administration affected the composition of salivary mycobiome communities. Furthermore, differences of salivary mycobiome in HIV infections after ART were complex and might mirror the immune state of the body.